2020
DOI: 10.3177/jnsv.66.449
|View full text |Cite
|
Sign up to set email alerts
|

A Diet Including Red Bell Pepper Juice and Soy Protein Suppress Physiological Markers of Muscle Atrophy in Mice

Abstract: Although muscle atrophy can be caused by disuse and lifestyle-related syndromes, it may be possible to prevent this condition through dietary intervention. We hypothesized that a diet including red bell pepper juice (RBPJ) and soy protein isolate (SPI) would prevent muscle atrophy. Accordingly, an experimental diet containing RBPJ and/or SPI was administered for 18 d to normal C57BL/6J mice. The control group was administered a casein diet. Four days before the end of the test period, denervation-induced muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Turinsky et al found that dissimilar concentrations of several free amino acids were identified in different types of myofibers; furthermore, increased concentrations of leucine and glutamic acid and a reduced level of glutamine and glycine were observed in denervation atrophied muscles [ 46 ]. Some studies proved that the concentration of glutathione declined in atrophic muscles due to reactive oxygen species, although Tachibana et al claimed that glutathione was highly detected in the denervation-induced muscle atrophy model; however, they speculated that the result was attributed to the brief duration of denervation [ 47 , 48 , 49 ]. Zhang et al found that glycerophospholipid metabolism and glutathione metabolism were significantly changed in breast muscle between slow-growth and fast-growth chickens, which were considered important functions in meat flavor [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Turinsky et al found that dissimilar concentrations of several free amino acids were identified in different types of myofibers; furthermore, increased concentrations of leucine and glutamic acid and a reduced level of glutamine and glycine were observed in denervation atrophied muscles [ 46 ]. Some studies proved that the concentration of glutathione declined in atrophic muscles due to reactive oxygen species, although Tachibana et al claimed that glutathione was highly detected in the denervation-induced muscle atrophy model; however, they speculated that the result was attributed to the brief duration of denervation [ 47 , 48 , 49 ]. Zhang et al found that glycerophospholipid metabolism and glutathione metabolism were significantly changed in breast muscle between slow-growth and fast-growth chickens, which were considered important functions in meat flavor [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mixed diet of soy protein and whey protein showed a strong inhibitory effect on denervation-induced skeletal muscle atrophy [ 143 ]. In addition, it has been reported that soy protein isolate and red bell pepper juice suppressed skeletal muscle atrophy in denervated mice [ 144 ]. Whey protein is known to stimulate muscle protein synthesis via mTOR signaling in humans [ 145 ].…”
Section: Natural Compounds (Effective Foods Against Denervation-induced Skeletal Muscle Atrophy)mentioning
confidence: 99%